Assessment of a computed tomography guided injection technique of the lumbo-sacral disc in sheep - Neveu, Fabienne; Vandeweerd, Jean-Michel; Kirschvink, Nathalie; Nozry, Kadhija; Gustin, Pascal; Dugdale, Alex; Bihin, Benoît; Nisolle, Jean-François (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
Objectives: Recent data indicate that degeneration of intervertebral discs occurs naturally in sheep, with a higher prevalence at the level of the lumbo-sacral disc. The objective of this ex vivo study was to evaluate a computed tomography (CT) guided method of injection into the ovine lumbo-sacral disc.Methods: Six euthanatized sheep were used for identification of the approach plane, the optimal direction of the needle and the mean distance from skin to disc. Dissection after injection of coloured ink was used to determine the anatomical structures that were penetrated. In seven other animals, all spines were assessed beforehand by CT and magnetic resonance imaging to determine whether disc pathology was present. The final position of the needle was assessed by CT to determine the accuracy of the technique. Contrast agent was injected to identify any problems associated with administration of liquid into the disc.Results: The CT guided injection technique was easy to perform and enabled adequate positioning of the needle into all (n = 7) lumbo-sacral discs. Distance between the skin and the disc ranged between 12 and 17 cm. No organ, vascular or nervous structure was penetrated and the needle path remained intramuscular without penetration of the peritoneal cavity. Contrast medium leaked out through three degenerate discs.Clinical significance: The current study described a consistently safe and accurate CT guided injection technique to the lumbo sacral disc for future in vivo experimental studies that will use sheep as animal model for human intervertebral disc disease disease.
Keywords: CT; computed tomography; injection; lumbosacral; intervertebral disc; sheep